Classroom environment and the transition to secondary schooling - Hine, Paul (Curtin University, 2001)
This study was undertaken to investigate changes in classroom environment as students move between upper primary and lower secondary school in selected schools in South Australia. A new instrument, the Middle School Classroom Environment Indicator (MSCEI), was devised to measure students' perceptions of particular aspects of classroom environment that were considered important in this transitional phase along the educational continuum. Actual and preferred versions of the instrument were used longitudinally with students in Grade 7 and again in Grade 8 in order to determine whether students perceived an improvement or deterioration in salient aspects of their classroom climate. Also, student satisfaction was assessed before and after transition. Quantitative data from the questionnaire were supported by qualitative data gathered through discussions with teachers, students and administrators, as well as classroom visits before and after transition into secondary school.Research questions were answered through numerous statistical analyses of questionnaire data: item analysis, factor analysis and analysis of variance for establishing the reliability and validity of the MSCEI; simple correlation and multiple regression analyses for investigating associations between student satisfaction and classroom environment scales; and paired t tests to compare and contrast perceptions of classroom environments in Grade 7 and Grade 8.The sample consisted of 311 students in six schools in Grade 7 and 575 students in six schools in Grade 8. The schools represented different enrolment profiles and 'distinctive settings. The schools involved were two single-sex boys' schools, one single-sex girls' school, and three co-educational schools. Five of the six schools in the sample had both primary and secondary classes in the school, while one school terminated enrolment as a primary school in Grade 7 and students moved to a new secondary setting in Grade 8.Classroom environments in secondary settings were generally perceived less favourably, given rapid lesson turnover, multiple specialist teachers and larger school sizes, which were associated with a perceived increase in alienation. These findings seem generally consistent across the sample of schools involved in the study, although variations were evident in different schools with differing enrolment profiles and internal arrangements for catering for students moving from primary to secondary schooling. Satisfaction was closely associated with the classroom environment dimensions of affiliation and autonomy in Grade 7, and with affiliation, autonomy and teacher support in Grade 8.Given the extensive work undertaken by researchers and scholars in the area of middle schooling, this study holds significance for teachers and administrators who wish to promote effective and manageable classroom experiences for students as they move from upper primary to lower secondary schooling.